Genomic and Transcriptomic Insights into Calcium Carbonate Biomineralization by Marine Actinobacterium Brevibacterium linens BS258 - Zhu, Yuying; Ma, Ning; Jin, Weihua; Wu, Shimei; Sun, Chaomin (Frontiers in Microbiology, 2017)
Calcium carbonate (CaCO3) biomineralization has been investigated due to its wide range of scientific and technological implications, however, the molecular mechanisms of this important geomicrobiological process are largely unknown. Here, a urease-positive marine actinobacterium Brevibacterium lines BS258 was demonstrated to effectively form CaCO3 precipitates. Surprisingly, this bacterium could also dissolve the formed CaCO3 with the increase of the Ca2+ concentration. To disclose the mechanisms of biomineralization, the genome of B. lines BS258 was further completely sequenced. Interestingly, the expression of three carbonic anhydrases was significantly up-regulated along with the increase of Ca2+ concentration and the extent of calcite dissolution. Moreover, transcriptome analyses revealed that increasing concentration of Ca2+ induced KEGG pathways including quorum sensing (QS) in B. lines BS258. Notably, most up-regulated genes related to QS were found to encode peptide/nickel ABC transporters, which suggested that nickel uptake and its associated urease stimulation were essential to boost CaCO3 biomineralization. Within the genome of B. lines BS258, there are both cadmium and lead resistance gene clusters. Therefore, the sequestration abilities of Cd2+ and Pb2+ by B. lines BS258 were checked. Consistently, Pb2+ and Cd2+ could be effectively sequestered with the precipitation of calcite by B. lines BS258. To our knowledge, this is the first study investigating the microbial CaCO3 biomineralization from both genomic and transcriptomic insights, which paves the way to disclose the relationships among bacterial metabolisms and the biomineralization.